Analisis Profil Keterampilan Berpikir Kritis dan Kreatif Siswa SMA pada Mata Pelajaran Biologi - Prasetyo Anggun Pribadi; Ary Susatyo Nugroho; Muhammad Syaipul Hayat (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to analyze the profile of senior high school students’ critical and creative thinking skills in Biology learning as part of developing 6C competencies. The method employed was descriptive quantitative research involving 33 students of class XI.10 at SMAN 1 Karanganyar, Kebumen Regency, selected through purposive sampling. Data were collected using essay tests of critical thinking skills based on Ennis’ indicators, creative thinking skills based on Torrance’s indicators, student perception questionnaires, and classroom observations. The data were analyzed descriptively using the mean score of each indicator. The results showed that the average score of students’ critical thinking skills based on the five Ennis indicators was 67.8%, categorized as moderate, while creative thinking skills based on Torrance’s indicators reached 55.56%, categorized as low. Students’ perception questionnaires indicated that both critical and creative thinking skills were in the high category with an average score of 73%. Classroom observation results supported the findings of the essay tests. In conclusion, students’ critical thinking skills in Biology learning are categorized as moderate, while their creative thinking skills are categorized as low.   Keywords: Biology, Creative Thinking, Critical Thinking, Profile, Senior High School Students.